Mechanism of the Vasodilator Effect of Mono-oxygenated Xanthones: A Structure-Activity Relationship Study - Diniz, Thiago F.; Pereira, Aline C.; Capettini, Luciano S. A.; Santos, Marcelo H.; Nagem, Tanus J.; Lemos, Virginia S.; Cortes, Steyner F. (Planta Medica, 2013)
The present study characterized the mechanisms involved in the vasodilator effect of two mono-oxygenated xanthones, 4-hydroxyxanthone and 4-methoxyxanthone. 9-Xanthenone, the base structure of xanthones, was used for comparison. 4-Hydroxyxanthone and 9-xanthenone induced a concentration-dependent and endothelium-independent vasodilator effect in arteries precontracted with phenylephrine (0.1 µmol · L−1) or KCl (50 mmol · L−1). 4-Methoxyxanthone induced a concentration-dependent vasodilator effect in arteries precontracted with phenylephrine, which was partially endothelium-dependent, and involved production of nitric oxide. In endothelium-denuded arteries precontracted with KCl, the vasodilator effect of 4-methoxyxanthone was abolished. The vasodilator effect of 4-hydroxyxanthone (96.22 ± 2.10 %) and 4-methoxyxanthone (96.57 ± 12.40 %) was significantly higher than observed with 9-xanthenone (53.63 ± 8.31 %). The presence of an oxygenated radical in position 4 made 4-hydroxyxanthone (pIC50 = 4.45 ± 0.07) and 4-methoxyxanthone (pIC50 = 5.04 ± 0.09) more potent as a vasodilator than 9-xanthenone (pIC50 = 3.92 ± 0.16). In addition, 4-methoxyxanthone was more potent than the other two xanthones. Ca2+ transients in vascular smooth muscle cells elicited by high K+ were abolished by 4-hydroxyxanthone and 9-xanthenone. The endothelium-independent effect of 4-methoxyxanthone was abolished by inhibition of K+ channels by tetraethylammonium. The current work shows that an oxygenated group in position 4 is essential to achieve Emax and to increase the potency of xanthones as vasodilators. Substitution of an OH by OCH3 in position 4 increases the potency of the vasodilator effect and changes the underling mechanism of action from the blockade of L-type calcium channels to an increase in NO production and activation of K+ channels.
Keywords: xanthones; 4-hydroxyxanthone; 4-methoxyxanthone; vasodilation; Ca2+ channels; nitric oxide; K+ channels